Importance of private ownership in the economy of Ukraine - Yarynovska, Mariana; Bozhok, Natalia (My University, 2014)
Dramatic transition to market economy and private property had the broad negative social consequences. The leading role in this process was played by rapid and outrageously unjust privatization of national property and by the ways it was distributed. As a result the phenomena of economic and/or property inequality, status inequality and inequality in access to various social benefits appeared in Ukrainian society. Political independence and transformational processes led to two phenomena. On the one hand, inequality relations have started development; on the other - scientists became aware that this phenomenon was part of scientific picture of the world.
Keywords: market economy; privatization; private ownership; ринкова економіка; приватизація; приватна власність; рыночная экономика; приватизация; частная собственность; кафедра ділової іноземної мови та міжнародної комунікації